Embracing God's future without forgetting the past : a conversation about loss, grief, and nostalgia in congregational life - Girlinghouse, Michael K. (Fortress Press, 2019)
Many congregations today are dealing with changes that have led to decline and significant loss. In Embracing God's Future without Forgetting the Past, Michael K. Girlinghouse argues that until a congregation comes to terms with its perceived losses through a healthy process of grief, it will be paralyzed in the present and unable to think creatively about the future. Acknowledging and expressing grief will give the congregation the courage to redefine its relationship with the past and draw strength and encouragement from its memories as it steps into the future. Drawing on more than thirty years of ministry experience in varied settings and concurrent study and teaching about loss, grief, and nostalgia, Girlinghouse shows clergy, church staff, and lay leaders how they can work through the experience of loss and grief, both personally and in their congregation. Part 1 discusses loss and grief using a contemporary, task-based model for the grief process. It also introduces recent research on the value of nostalgia. In part 2, Girlinghouse helps leaders tell their congregation's story, including its losses, examine how that story fits in our current social context, and explore ways to accept the reality of its losses and express grief over them. Part 3 considers ways congregations can think more adaptively and creatively about the future without forgetting or devaluing the past. Girlinghouse presents appreciative inquiry as a tool to discover and build on a congregation's strengths while coming to terms with its losses. Part 4 is about embracing God's future for the congregation, "remembering forward," and making the changes necessary to move from the sadness of loss to the joy of taking up life again. Each chapter includes a Bible study and questions for reflection and discussion